High-voltage-resistant lithium battery positive electrode slurry dispersing agent as well as preparation method and application thereof

By developing a specific lithium battery positive slurry dispersant and using specific monomer combinations to form a protective film that withstands high voltage, the problem of deterioration of existing dispersants at high voltage is solved, and the lithium battery at high voltage is realized stability and safety.

CN119390902APending Publication Date: 2025-02-07SHENGHONG KINETIC ENERGY TECH (TAIZHOU) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411514097.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing lithium battery positive electrode dispersants are prone to electrochemical oxidation side reactions under high voltage, resulting in deterioration of battery performance or safety hazards, and it is difficult to maintain stability at high voltage.

Method used

Develop a lithium battery positive electrode slurry dispersant through a specific monomer combination, including aromatic ring and/or organic amine polymeric monomer, olefinic polymeric monomer and carbon fluorine bond/phosphorus carbon double bond The polymerization of monomers forms a high voltage-resistant protective film, inhibits the oxidation and reduction decomposition of solvents, and reduces the dissolution of transition metal elements.

Benefits of technology

The dispersant remains stable at a voltage of up to 6V, which significantly improves the dispersion effect of the positive electrode material and conductive agent of lithium battery, reduces the viscosity of the battery, and improves the energy density and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390902A_ABST
    Figure CN119390902A_ABST
Patent Text Reader

Abstract

The invention provides a high-voltage-resistant lithium battery positive electrode slurry dispersing agent as well as a preparation method and application thereof. The monomer components for preparing the lithium battery positive electrode slurry dispersant comprise 10%-15% of a polymeric monomer containing aromatic nucleus and / or organic amine, 5%-10% of a polymeric monomer containing phosphate and / or carboxylate and / or sulfonate, 65%-75% of an olefin polymeric monomer and 5%-15% of a polymeric monomer containing a fluorocarbon bond / phosphorus-carbon double bond. The dispersing agent disclosed by the invention is excellent in dispersing effect, has a good dispersing effect on positive electrode main materials (LFP, LCO, NCM and the like) and conductive agent materials (CNT, SP and the like), and has great advantages on viscosity reduction, solid improvement, coating, impedance reduction and the like; and the high-voltage resistance is good, and the withstand voltage is up to 6V.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a high-voltage lithium battery positive electrode slurry dispersant, a preparation method and an application thereof. Background Art

[0002] Energy density and safety are the two main research directions of the lithium-ion battery industry. The energy density of lithium-ion batteries is determined by the battery capacity and the charge and discharge voltage. Therefore, in order to improve the energy density of the battery, it is necessary to increase the charging cut-off voltage or adopt a new high-energy density lithium battery material system. At present, the positive electrode materials used include lithium cobalt oxide, lithium manganese oxide, ternary materials, lithium iron phosphate and lithium iron manganese phosphate materials. In the prior art, the application fields with extremely high requirements for the energy density of lithium batteries have increased the charging cut-off voltage year by year. The charging cut-off voltage of modified lithium cobalt oxide has reached 4.6V, the charging cut-off voltage of lithium iron manganese phosphate is 4.1V, and some ternary materials are also around 4.7V. Therefore, as the use conditions of the positive electrode become more and more harsh, the dispersant material used in the positive electrode needs to be functionally designed and have certain high voltage resistance performance. In addition, the basic requirements of the dispersant itself, namely the dispersion performance, cannot be lost. For example, materials such as lithium iron phosphate and lithium iron manganese phosphate have small particle sizes and are more difficult to disperse, which tests the dispersibility of the dispersant.

[0003] Conventional dispersants may undergo electrochemical oxidation side reactions under high voltage, leading to degradation of battery performance and even dangers such as battery combustion or explosion. Currently, commonly used dispersants have become a major obstacle to the development of high-voltage batteries. For example, polyvinylpyrrolidone (PVP), a widely used dispersant in battery slurry, can ensure good dispersibility but can only withstand a voltage of 4V; CN115763808A discloses a high-voltage resistant dispersant that can remain stable within 2 to 6V, but it is only for conductive agent slurry and the dispersion effect can generally only be comparable to that of existing products.

[0004] Therefore, the art is in urgent need of developing a high-voltage resistant positive electrode slurry dispersant to achieve a good dispersion effect on both the positive electrode main material and the conductive agent material, and to have high-voltage resistance. Summary of the invention

[0005] Based on the defects of the prior art, the first purpose of the present invention is to provide a lithium battery positive electrode slurry dispersant; the second purpose of the present invention is to provide a method for preparing the lithium battery positive electrode slurry dispersant; the third purpose of the present invention is to provide an application of the lithium battery positive electrode slurry dispersant in the preparation of lithium battery positive electrode slurry.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] In one aspect, the present invention provides a lithium battery positive electrode slurry dispersant, wherein the monomer components for preparing the dispersant include, by mass percentage, 100%:

[0008]

[0009] The present invention develops a high-voltage resistant positive electrode slurry dispersant, which has excellent dispersing effect, has good dispersing effect on positive electrode main materials (LFP, LCO, NCM, etc.) and conductive agent materials (CNT, SP, etc.), and has great advantages in viscosity reduction, solidification, coating, impedance reduction, etc.; and has good high-voltage resistance, and functional monomers can preferentially react with solvent molecules in the electrolyte to form an effective protective film on the electrode surface to improve interface stability, inhibit subsequent oxidation and reduction decomposition of the solvent, and can effectively reduce the dissolution of transition metal elements, so that the dispersant has better high-voltage resistance and a withstand voltage of up to 6V.

[0010] In the above-mentioned lithium battery positive electrode slurry dispersant, preferably, the aromatic ring and / or organic amine-containing polymer monomer is selected from one or more combinations of 1,3-benzenediol, benzoic acid, 2-ethylhexylamine, hexylamine and octylamine, but is not limited thereto.

[0011] The aromatic ring and / or organic amine-containing polymerizable monomer of the present invention is a polymerizable monomer containing an aromatic ring, amines and the like.

[0012] In the above-mentioned lithium battery positive electrode slurry dispersant, preferably, the phosphate and / or carboxylate and / or sulfonate-containing polymerization monomer is selected from one or a combination of two or more of alkyl alcohol ether sulfosuccinate diester sodium salt, allyl polyether ammonium phosphate salt, alkyl sulfosuccinate sodium salt and allyl sodium sulfonate, but is not limited thereto.

[0013] The phosphate and / or carboxylate and / or sulfonate-containing polymer monomers of the present invention are polymer monomers containing salt substances such as phosphoric acid, carboxylic acid, and sulfonic acid.

[0014] In the above-mentioned lithium battery positive electrode slurry dispersant, preferably, the olefin polymerizable monomer is selected from one or more combinations of ethylene, styrene, allylbenzene and methylstyrene, but is not limited thereto.

[0015] The olefin polymer monomer of the present invention is a polymer monomer of an alkane or olefin chain having a long carbon chain structure.

[0016] In the above-mentioned lithium battery positive electrode slurry dispersant, preferably, the polymerizable monomer containing carbon-fluorine bond / phosphorus-carbon double bond is selected from one or more combinations of fluoroanisole, fluorophenylene sulfide and ethylene phosphine, but is not limited thereto.

[0017] On the other hand, the present invention also provides a method for preparing the above-mentioned lithium battery positive electrode slurry dispersant, the method comprising the following steps:

[0018] Step 1, stirring and mixing an organic solvent, a polymer monomer containing an aromatic ring and / or an organic amine, and an olefin polymer monomer to obtain a mixed solution;

[0019] Step 2, heating the mixed solution under a nitrogen atmosphere, and adding an initiator to stir the mixture to obtain a reaction solution;

[0020] Step three, continue to add initiator, phosphate and / or carboxylate and / or sulfonate-containing polymerization monomers, and carbon-fluorine bond / phosphorus-carbon double bond-containing polymerization monomers to the reaction solution, maintain the heating temperature and continue stirring the reaction to obtain a dispersant.

[0021] In the above preparation method, preferably, the organic solvent is selected from one or more combinations of N-vinyl pyrrolidone, N-formyl dimethylamine and acetyl dimethylamine, but is not limited thereto.

[0022] In the above preparation method, preferably, the amount of the organic solvent used is 1 to 3 times the total mass of the monomers.

[0023] In the above preparation method, preferably, the initiator is selected from azobisisobutyronitrile and / or benzoyl peroxide, but is not limited thereto.

[0024] In the above preparation method, preferably, the amount of the initiator used is 0.5% to 2.5% of the total weight of the monomers.

[0025] In the above preparation method, preferably, in step 2, the temperature of the heating and stirring reaction is 50-100° C., and the stirring reaction time is 4-9 h.

[0026] In the above preparation method, preferably, in step three, the temperature of the heating and stirring reaction is 50-100° C., and the stirring reaction time is 3-7 h.

[0027] In another aspect, the present invention also provides the use of the above-mentioned lithium battery positive electrode slurry dispersant or the lithium battery positive electrode slurry dispersant prepared by the above-mentioned preparation method in the preparation of lithium battery positive electrode slurry.

[0028] Beneficial effects of the present invention:

[0029] The lithium battery positive electrode slurry dispersant of the present invention:

[0030] (1) It has good dispersibility for conductive agents (CNT, SP, etc.) and positive electrode materials (LFP, LCO, NCM, etc.); using it to prepare positive electrode slurry for lithium batteries can significantly improve the preparation efficiency and reduce the preparation cost, and it has excellent effects during mixing and coating operations;

[0031] (2) It has high stability and excellent viscosity reduction effect. The prepared slurry has low viscosity rebound after 24 hours, 48 ​​hours or even one month;

[0032] (3) It has excellent impedance reduction effect, and has advantages over electrode resistance and four-probe;

[0033] (4) Small addition amount can exert good dispersibility and be beneficial to battery energy utilization;

[0034] (5) It has good high voltage resistance and can withstand voltage up to 6V.

[0035] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 This is a comparison chart of the cyclic voltammetry test experiment of the button prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only some embodiments of the present invention, rather than all embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The process, conditions, reagents, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art, and the present invention does not particularly limit the contents.

[0039] Embodiment 1:

[0040] This embodiment provides a lithium battery positive electrode slurry dispersant. The monomer components for preparing the dispersant include, by mass percentage, 100%:

[0041] Component A: hexylamine 12%;

[0042] Component B: allyl polyether ammonium phosphate 8%;

[0043] Component C: styrene 70%;

[0044] Component D: 10% fluoroanisole.

[0045] This embodiment also provides a method for preparing a lithium battery positive electrode slurry dispersant, the preparation method further comprising adding 3.5 times the total mass of the above-mentioned monomers as an organic solvent N-vinyl pyrrolidone and 2% of the total mass of the monomers as an initiator azobisisobutyronitrile; the specific preparation method is as follows:

[0046] (1) Add hexylamine, styrene and N-vinyl pyrrolidone to a 2L five-necked round-bottom flask equipped with a nitrogen device, a stirring device, a reflux condenser and a thermometer, rotate at 60 r / min, stir for 5 min, and stir to obtain a mixed solution;

[0047] (2) passing nitrogen gas, heating to 60° C. in a nitrogen atmosphere, then adding an initiator, azobisisobutyronitrile (0.8%), maintaining the temperature at 75° C., stirring continuously at a speed of 60 r / min, reacting for 5 h, and obtaining a reaction solution;

[0048] (3) Then, an initiator, azobisisobutyronitrile (1.2%), was added and the reaction was continued for 10 min. Then, allyl polyether ammonium phosphate and fluoroanisole were added and the reaction was continued with stirring at a speed of 60 r / min for 4 h to stop the reaction and obtain a dispersant.

[0049] Embodiment 2:

[0050] This embodiment provides a lithium battery positive electrode slurry dispersant. The monomer components for preparing the dispersant include, by mass percentage, 100%:

[0051]

[0052] This embodiment also provides a method for preparing a lithium battery positive electrode slurry dispersant, the preparation method further comprising adding 3.5 times the total mass of the above-mentioned monomers as an organic solvent N-vinyl pyrrolidone and 2% of the total mass of the monomers as an initiator azobisisobutyronitrile; the specific preparation method is as follows:

[0053] (1) In a 2L five-necked round-bottom flask equipped with a nitrogen device, a stirring device, a reflux condenser and a thermometer, octylamine, ethylene and N-vinyl pyrrolidone were added, the speed was 60 r / min, and the mixture was stirred for 5 min to obtain a mixed solution;

[0054] (2) passing nitrogen gas, heating to 60° C. in a nitrogen atmosphere, then adding an initiator, azobisisobutyronitrile (0.8%), maintaining the temperature at 75° C., stirring continuously at a speed of 60 r / min, reacting for 5 h, and obtaining a reaction solution;

[0055] (3) Then, an initiator, azobisisobutyronitrile (1.2%), was added and the reaction was continued for 10 minutes. Then, sodium allyl sulfonate and ethylene phosphine were added and the reaction was continued for 4 hours with stirring at 60 r / min to obtain a dispersant.

[0056] Embodiment 3:

[0057] This embodiment provides a method for preparing a thin film composite containing MWCNTs using a CNT conductive slurry. The specific preparation method includes:

[0058] CNT (non-purified MWCNT FT7000, with an outer diameter of 5 to 10 nm, prepared by CNano Inc. Co.) was dissolved in 380 g of NMP using 4 g of the dispersant obtained in the comparative group PVP K30, Examples 1 and 2, and 16 g of CNT was added. A vertical tank was used and 400 g of 0.3 mm zirconium beads were added. The mixture was subjected to mechanical grinding treatment for 4 h at room temperature (about 25 ° C) to obtain a black MWCNT-containing dispersion. Finally, the zirconium beads were filtered to obtain a CNT dispersion liquid, which was uniformly dispersed without precipitation. 3 g of the filtered CNT dispersion liquid was taken out, coated on PET using a 20 μm gap scraper, and baked at 120 ° C for 1 h to prepare a thin film composite containing MWCNT.

[0059] The conductivity test experiment was conducted on the prepared MWCNT-containing thin film composite, and the conductivity was specifically tested using a four-probe resistance meter. The results are shown in Table 1 below.

[0060] Table 1

[0061]

[0062] It can be seen from the experimental results in Table 1 that compared with the control group, the MWCNT film composite obtained by using the dispersants of Examples 1 and 2 of the present invention has high stability, low slurry viscosity, excellent viscosity reduction effect, low 24h and 48h viscosity rebound, and excellent impedance reduction effect.

[0063] This embodiment also provides a preparation of a button battery, specifically: 3g of the filtered CNT dispersion liquid is taken out, coated on an aluminum foil using a 20μm gap scraper and assembled with a lithium sheet into a CR2032 type button battery, with a porous glass fiber as a separator and an electrolyte of 1MLiTFSI-AND, and the assembled button battery is subjected to a cyclic voltammetry test, and the test results are as follows Figure 1 shown.

[0064] Depend on Figure 1The experimental results show that the control group has an oxidation peak at a voltage of less than 4V, and oxidative decomposition occurs when the voltage exceeds 4V, while Examples 1 and 2 do not have an oxidation current at 2.5-6.5V, indicating that the high-voltage resistant dispersant of the present invention can withstand a voltage of more than 6V without oxidative decomposition.

[0065] Embodiment 4:

[0066] This embodiment provides a method for preparing a lithium battery positive electrode slurry and assembling a lithium ion battery using the CNT conductive slurry prepared in Example 3.

[0067] The preparation method of lithium battery positive electrode slurry is as follows:

[0068] First, 18 g of the binder PVDF was dissolved in 400 g of N-methylpyrrolidone solvent to prepare a solution, and 564 g of NCM (nickel cobalt manganese) and 18 g of the three CNT conductive slurries prepared in Example 3 were added in sequence at a speed of 120 r / min and stirred for 30 min to allow the powder materials to be fully and evenly mixed in the solvent to obtain NCM positive electrode slurry.

[0069] The method of assembling lithium-ion batteries is as follows:

[0070] The positive electrode slurry was mixed and coated on aluminum foil, and then dried overnight at 110°C in a vacuum to prepare the positive electrode. 95% graphite, 1.5% conductive carbon, 1.5% sodium carboxymethyl cellulose and 2% styrene butadiene rubber were mixed and coated on copper foil, and then dried overnight at 60°C in a vacuum to prepare the negative electrode. 1 mol of LiPF6 was used as the lithium salt, the solvent was a mixed solvent composed of EC / DC / EMC (volume ratio of 1:1:1) as the electrolyte, and porous glass fiber was used as the separator to assemble the lithium-ion battery.

[0071] The assembled lithium-ion battery was subjected to a membrane resistivity test experiment and a capacity retention rate test experiment. The experimental results are shown in Tables 2 and 3 below.

[0072] Table 2

[0073]

[0074] Table 3

[0075]

[0076] It can be seen from the experimental results in Table 2 that compared with the control group, the NCM positive electrode slurry obtained by using the dispersants of Examples 1 and 2 of the present invention has low viscosity, excellent viscosity reduction effect, low viscosity rebound after 24h and 48h, and has excellent dispersion, viscosity reduction and impedance reduction effects.

[0077] It can be seen from the experimental results in Table 3 that compared with the control group, the batteries prepared using the dispersants of Examples 1 and 2 of the present invention have high initial efficiency, and the charging cut-off value is as high as 4.7V, and the cycle performance is excellent, and the capacity retention rate is high.

[0078] Embodiment 5:

[0079] This embodiment provides a method for preparing a lithium battery positive electrode slurry and assembling a lithium ion battery using the CNT conductive slurry prepared in Example 3.

[0080] The preparation method of lithium battery positive electrode slurry is as follows:

[0081] First, 18 g of the binder PVDF was dissolved in 400 g of N-methylpyrrolidone solvent to prepare a solution, and 564 g of LCO (lithium cobalt oxide) and 18 g of the three CNT conductive slurries prepared in Example 3 were added in sequence at a rotation speed of 120 r / min and stirred for 30 min to allow the powder materials to be fully and evenly mixed in the solvent to obtain LCO positive electrode slurry.

[0082] The method of assembling lithium-ion batteries is as follows:

[0083] The positive electrode slurry was mixed and coated on aluminum foil, and then dried overnight at 110°C in a vacuum to prepare the positive electrode. 95% graphite, 1.5% conductive carbon, 1.5% sodium carboxymethyl cellulose and 2% styrene butadiene rubber were mixed and coated on copper foil, and then dried overnight at 60°C in a vacuum to prepare the negative electrode. 1 mol of LiPF6 was used as the lithium salt, the solvent was a mixed solvent composed of EC / DC / EMC (volume ratio of 1:1:1) as the electrolyte, and porous glass fiber was used as the separator to assemble the lithium-ion battery.

[0084] The assembled lithium-ion battery was subjected to a membrane resistivity test experiment and a capacity retention rate test experiment. The experimental results are shown in Tables 4 and 5 below.

[0085] Table 4

[0086]

[0087] Table 5

[0088]

[0089] It can be seen from the experimental results in Table 4 that compared with the control group, the LCO positive electrode slurry obtained by using the dispersants of Examples 1 and 2 of the present invention has low viscosity, excellent viscosity reduction effect, low viscosity rebound after 24h and 48h, and has excellent dispersion, viscosity reduction and impedance reduction effects.

[0090] It can be seen from the experimental results in Table 5 that compared with the control group, the batteries prepared using the dispersants of Examples 1 and 2 of the present invention have high initial efficiency, and the charging cut-off value is as high as 4.6V, and the cycle performance is excellent, and the capacity retention rate is high.

[0091] Embodiment 6:

[0092] This embodiment provides a method for preparing a lithium battery positive electrode slurry and assembling a lithium ion battery using the CNT conductive slurry prepared in Example 3.

[0093] The preparation method of lithium battery positive electrode slurry is as follows:

[0094] First, 18 g of the binder PVDF was dissolved in 400 g of N-methylpyrrolidone solvent to prepare a solution, and 564 g of LFP (lithium iron phosphate) and 18 g of the three CNT conductive slurries prepared in Example 3 were added in sequence at a rotation speed of 120 r / min and stirred for 30 min to allow the powder materials to be fully and evenly mixed in the solvent to obtain LFP positive electrode slurry.

[0095] The method of assembling lithium-ion batteries is as follows:

[0096] The positive electrode slurry was mixed and coated on aluminum foil, and then dried overnight at 110°C in a vacuum to prepare the positive electrode. 95% graphite, 1.5% conductive carbon, 1.5% sodium carboxymethyl cellulose and 2% styrene butadiene rubber were mixed and coated on copper foil, and then dried overnight at 60°C in a vacuum to prepare the negative electrode. 1 mol of LiPF6 was used as the lithium salt, the solvent was a mixed solvent composed of EC / DC / EMC (volume ratio of 1:1:1) as the electrolyte, and porous glass fiber was used as the separator to assemble the lithium-ion battery.

[0097] The assembled lithium-ion battery was subjected to a membrane resistivity test experiment and a capacity retention rate test experiment. The experimental results are shown in Tables 6 and 7 below.

[0098] Table 6

[0099]

[0100] Table 7

[0101]

[0102] It can be seen from the experimental results in Table 6 that compared with the control group, the LFP positive electrode slurry obtained by using the dispersants of Examples 1 and 2 of the present invention has low viscosity, excellent viscosity reduction effect, low viscosity rebound after 24h and 48h, and has excellent dispersion, viscosity reduction and impedance reduction effects.

[0103] It can be seen from the experimental results in Table 7 that compared with the control group, the batteries prepared using the dispersants of Examples 1 and 2 of the present invention have high initial efficiency and high capacity retention rate.

[0104] The present invention uses specific embodiments to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A lithium battery positive electrode slurry dispersant, wherein the monomer components for preparing the dispersant include, by mass percentage, 100%:

2. The lithium battery positive electrode slurry dispersant according to claim 1, characterized in that: The aromatic ring and / or organic amine-containing polymer monomer is selected from one or more combinations of 1,3-benzenediol, benzoic acid, 2-ethylhexylamine, hexylamine and octylamine.

3. The preparation method according to claim 1, characterized in that: The phosphate and / or carboxylate and / or sulfonate-containing polymer monomer is selected from one or a combination of two or more of alkyl alcohol ether sulfosuccinate sodium salt, allyl polyether ammonium phosphate salt, alkyl sulfosuccinate sodium salt and allyl sodium sulfonate.

4. The lithium battery positive electrode slurry dispersant according to claim 1, characterized in that: The olefin polymerizable monomer is selected from one or more combinations of ethylene, styrene, allylbenzene and methylstyrene.

5. The lithium battery positive electrode slurry dispersant according to claim 1, characterized in that: The polymerizable monomer containing a carbon-fluorine bond / phosphorus-carbon double bond is selected from one or more combinations of fluoroanisole, fluorophenylene sulfide and ethylene phosphine.

6. The method for preparing the lithium battery positive electrode slurry dispersant according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: Step 1, stirring and mixing an organic solvent, a polymer monomer containing an aromatic ring and / or an organic amine, and an olefin polymer monomer to obtain a mixed solution; Step 2, heating the mixed solution under a nitrogen atmosphere, and adding an initiator to stir the mixture to obtain a reaction solution; Step three, continue to add initiator, phosphate and / or carboxylate and / or sulfonate-containing polymerization monomers, and carbon-fluorine bond / phosphorus-carbon double bond-containing polymerization monomers to the reaction solution, maintain the heating temperature and continue stirring the reaction to obtain a dispersant.

7. The preparation method according to claim 6, characterized in that: The organic solvent is selected from a combination of one or more of N-vinyl pyrrolidone, N-formyl dimethylamine and acetyl dimethylamine; Preferably, the amount of the organic solvent used is 1 to 3 times the total mass of the monomers.

8. The preparation method according to claim 6, characterized in that: The initiator is selected from azobisisobutyronitrile and / or benzoyl peroxide; Preferably, the amount of the initiator used is 0.5% to 2.5% of the total weight of the monomers.

9. The preparation method according to claim 6, characterized in that: In step 2, the temperature of the heating and stirring reaction is 50 to 100° C., and the stirring reaction time is 4 to 9 hours; Preferably, in step three, the temperature of the heating and stirring reaction is 50-100° C., and the stirring reaction time is 3-7 h.

10. Use of the lithium battery positive electrode slurry dispersant according to any one of claims 1 to 5 or the lithium battery positive electrode slurry dispersant prepared by the preparation method according to any one of claims 6 to 9 in preparing lithium battery positive electrode slurry.

Citation Information

Patent Citations

  • High-voltage-resistant conductive slurry dispersing agent

    CN115763808A